IMPLEMENTASI ELEKTRONIK JUSTICE SYSTEM E-COURT DALAM PROSES BERPERKARA TINGKAT PERTAMA DI PENGADILAN NEGERI PEKANBARU BERDASARKAN PERATURAN MAHKAMAH AGUNG NO 1 TAHUN 2019 TENTANG ADMINISTRASI PERKARA DAN PERSIDANGAN DI PENGADILAN SECARA ELEKTRONIK - Zahra, Tasya Alfiya; Firdaus, Emilda; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
A person with visual impairment is any person who has limited vision dueto one thing or another who in interacting with the environment experiencesobstacles and difficulties to participate fully and effectiveli in the socia. E-Courtis an instrument in court as a form of service to the public in terms of online caseregistration, online payments, online summons, and online trials. The E-Courtapplication itself is an implementation of information technology where thegovernment must be sharp in seeing opportunities with the presence oftechnology, so an internet-based application called E-Court was created.In accordance with the background above, the author formulates the mainproblem to be studied, namely: 1) How is the Justice Information System (E-Court) implemented in the Pekanbaru District Court? 2). What are the inhibitingfactors faced in implementing the E-Court application at the Pekanbaru DistrictCourt? 3). What are the appropriate efforts to optimize the implementation of theE-Court application at the Pekanbaru District Court?Based on the research results, it is known that the implementation of theJustice Information System (E-Court) at the Pekanbaru District Court is aneffective, efficient and hassle-free process, carried out quickly and case costsincurred can be borne by the case parties. Furthermore, monitoring andevaluation of the performance of all ASNs in implementing the E-Court within thePekanbaru District Court, and to the community in the jurisdiction of thePekanbaru Court and carry out recruitment of additional employees at thePekanbaru District Court whose functions are assigned specifically to the E-Court Corner.Keywords: Implementation, E-Court, Pekanbaru District Court.